Receiving Irrigation and Drinking Water Together with Electricity in Remote and Arid Areas Using Membrane Desalination Device - Hakobyan, A. R.; Alanezi, A. A.; Hakobyan, A. A.; Minasyan, K. Zh. (ՀԱԱՀ հիմնադրամ)
The availability of irrigation and drinking water, as well as water supply for agricultural purposes are important requirements for living in remote areas. The hybrid desalination device has been designed and tested under field conditions. In the mentioned device the electricity is produced with the help of absorbing solar energy by PV panels and water desalination process is performed due to thermal amount released from its heating. The novelty of this system is the structure of the device, which combines a PV panel and a MD desalination unit. The pilot plant had a total yield of 9.6 kg/m2 and 680 W h/m2day. The suggested device is a self-supply one that produces water for aeroponic and hydroponic (of drip and flow style) irrigation systems. It is also a means for satisfying the needs of drinking water and electricity.
Keywords: Agricultural Engineering